80 PPCI: is there a role for the ACS ANP?. (9th June 2011) - Oriolo, V; Tagney, J
Abstract : Introduction: Primary Percutaneous Coronary Intervention (PPCI) is now considered the treatment of choice for patients experiencing ST Elevation Myocardial Infarction (STEMI) (European Society of Cardiology/European Association for Cardio-Thoracic Surgery 2010). One of the many benefits claimed is reduced length of stay due to decreased morbidity (Zahn et al 2000, Kalla et al 2006). To assess performance of one English PPCI 24/7 provider organisation against the national average length of stay (LOS) for patients post PPCI, a retrospective baseline audit was conducted. This demonstrated an average LOS of 4.4 days which is above the National Infarct Angioplasty Project 2008 average LOS of 3 days. A 48 h nurse led discharge (NLD) protocol was therefore developed and introduced by the acute coronary syndromes advanced nurse practitioner to streamline the patient journey. This instructed the nurse and/or physician to ensure appropriate investigation and documentation was carried out in a timely manner to avoid unnecessary delays in patient discharge. Method: Suitability criteria for the 48-h NLD protocol were established, which included: absence of acute complications (eg, : bleeding, haemodynamic instability, ongoing chest pain, ejection fraction <40%, respiratory compromise); appropriate support at discharge. Following the baseline audit, data were electronically collected prospectively for 5 months, measuring date of admission to date of discharge to the usual place of residence. After 5 months the audit was repeated to assess the average length of stay for patients presenting with STEMI. Result: Between 1st April 2010 and 31st August 2010, a total of 274 patients were admitted with STEMI. Of these, 122 (45%) met the NLD criteria and were discharged by the ACS ANP. The remaining 152 (55%) were discharged by the medical physicians. It was noted that introduction of the protocol also facilitated a structured approach to discharge for the medical team. The average LOS for all PPCI patients (n=274) decreased from 4.4 days to 3 days (30%). For patients that were seen and discharged solely by the advanced nurse practitioner (n=122), the average LOS decreased from 4.4 days to 2.0 days (55%). Conclusions/Implications: In the current financial climate, a decrease in LOS can have a significant impact on any organisational resources thus increasing efficiency saving and patient throughput. This demonstrates part of the added value the advanced nurse practitioner brings to patient care and to tertiary centres that provide a 24/7 PPCI service.